Transcription Factor GFI1B in Health and Disease - Anguita, Eduardo; Candel, Francisco J.; Chaparro, Alberto; Roldán-Etcheverry, Juan J. (Frontiers in Oncology, 2017)
Many human diseases arise through dysregulation of genes that control key cell fate pathways. Transcription factors are major cell fate regulators frequently involved in cancer, particularly in leukemia. The GFI1B gene, coding a transcription factor, was identified by sequence homology with the oncogene GFI1 (Growth Factor Independence 1). Both GFI1 and GFI1B have six C-terminal C2H2 zinc-fingers and an N-terminal SNAG (SNAIL/GFI1) transcriptional repression domain. Gfi1 is essential for neutrophil differentiation in mice. In humans, GFI1 mutations are associated with severe congenital neutropenia. Gfi1 is also required for B and T lymphopoiesis. However, knockout mice have demonstrated that Gfi1b is required for development of both erythroid and megakaryocytic lineages. Consistent with this, human mutations of GFI1B produce bleeding disorders with low platelet count and abnormal function. Loss of Gfi1b in adult mice increases the absolute numbers of hematopoietic stem cells (HSCs) that are less quiescent than wild-type HSCs. In keeping with this key role in cell fate, GFI1B is emerging as a gene involved in cancer, which also includes solid tumors. In fact, abnormal activation of GFI1B and GFI1 has been related to human medulloblastoma and is also likely to be relevant in blood malignancies. Several pieces of evidence supporting this statement will be detailed in this mini review.